Risk Assessment and Analysis for A Task in The Context of The Work Process - Dorota WOJTYTO; Joanna MICHALIK; Szymon BERSKI (Communications of International Proceedings, 2022)
The article presents a risk assessment and analysis for a task in the context of the work process at the work position of a glass quality control operator. The main tasks that are performed by the employee during the work process were defined, then the hazards related to each activity were identified, and preventive actions minimizing the occurrence of this hazard were proposed. On this basis, in order to carry out a risk assessment and analysis, criteria that take into account actual exposure to risk, probability, and effects when using a proper methodology have been determined. The individual stages of the risk management process, which are implemented in the discussed case, take into account the provisions of the ISO 31000:2018 and ISO 45001:2018 standards, as well as other risk management standards. The main aim of this article was an attempt to answer the following questions: how to properly identify and analyze risks in work processes in order to effectively prevent hazards and ensure broadly understood employee safety? How to effectively develop a risk management methodology adapted to the needs of a given organization?
Keywords: Risk Management; Work Processes; Occupational Risk; Risk Management Standards.